HUKUM PERNIKAHAN DI BAWAH TANGAN (SIRRI) (TINJAUAN UNDANG-UNDANG NO: 1 TAHUN 1974 DIRUBAH UNDANG-UNDANG NO: 16 TAHUN 2019 TENTANG PERKAWINAN) - Ihya', Rachmat; Wahyuni, Umi (JURNAL LEGISIA, 2021)
Marriage is an important event in people's lives, so the state has the right to regulate this matter in clear rules to provide legal protection and order in people's lives. about the phenomenon of marriage that is not uncommon but often occurs in the community, namely underhand marriage or in Islamic terms, sirri marriage. The issue of legal or unregistered marriages often becomes a polemic which results in unclear marital status that occurs, this has a negative impact on the parties involved, both wives, husbands and children. research on the behavior of these community groups (the perpetrators of sirri marriages) in society, what are the causes of underhand marriages (sirri) in society and the legal impact. This study uses a normative juridical method with a statutory approach as the main source of legal material, marriage according to the Islamic Law Compilation is that marriages carried out outside the supervision of the Marriage Registrar have no legal force. Keywords: Legal Review, Sirri marriage, Society